INTERLEUKIN -2 ( IL-2 ) AND GAMMA INTERFERON ( IFN ? ) OF LYMPHOCYTE CULTURE SUPERNATANT IN IRON DEFICIENCY ANEMIA PATIENTS WITH INFECTION - Suega, Ketut; Bakta, I M; Sudewa D., AAG; Suata, Ketut (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol. 4, No. 1 Januari 2010, 2012)
Iron is an essential nutrient for every living cells because of it role as molecule fortransport of oxygen, as well as DNA synthesis through synthesis of ribonucleotidereductase. Iron deficiency anemia patients, especially pregnant women and children aremore susceptible to infection because of deterioration of their immune response. This wassupported by findings of decreased in phagocytic activities of white blood cells and Tcelllymphocyte proliferation impairment. Iron deficiency anemia (IDA) patients alsoaffect working capacities hence diminishing working outcomes. Although the underlyingmechanism of immune defect in iron deficiency anemia is not clearly understood,multifactor events considered play their contributing roles such as abnormality ofribonucleotide reductase enzym, impairment of T-cell proliferation and activities, alteredcytokine production of IL-2 and IFN?.The study was done to asses the relationship of IL-2 and gamma IFN withinfection in IDA patients on lymphocyte culture supernatant of IDA patients. Study wasconducted on cross-sectional analytic design. Sixty-four iron deficiency anemia patientstreated in Sanglah General Teaching Hospital were recruited, and 31 (48.4%) out of 64IDA patients were man and 33 (51.6%) women, have been selected for the study. Thisstudy found 17 (26.7%) IDA patients with infection, aged 38 ± 14.48 years and 47(73.3%) IDA patients without infection, with age average of 40.5 ± 14.4 years. Allvariables of data characteristics examined did not indicate any statistical significantdifference between group of IDA patients with infection and those without infection. Theaverage level of hemoglobin between the two groups did not differ statistically. Similarresult was obtained if samples were differentiated into severe (Hb< 7g/dl) and mildanemia. The study also revealed that there were no differences of cytokine level observedbetween older and younger age (upper and below 44.5 years) in IDA patients withinfection and without infection. Furthermore, no differences of cytokine level were foundbased on gender between IDA male 10.9 (8.60 – 12,65) (pg/l) patients and IDA femalepatients 10.6 (7.50 – 13.43) (pg/l) with Z -0.490, p =0.624. Nevertheless, significantdifferences were noted between supernatant of IL-2 and IFN? in IDA patients withinfection when compared to IDA patients without infection (Z= - 2.509, p= 0.012 forsupernatant IL-2; and Z= -2.569, p= 0.010 for supernatant IFN?).The study conclusion is that level of IL-2 and IFN? from lymphocyte culturesupernatant of patient suffered from IDA with infection is significantly lower whencompared to IDA patient without infection. It therefore summarized that lower level ofIL-2 and gamma IFN in patients suffered from iron deficiency impaired their immune response to certain infections therefore this findings support the theory that IDA patientsmore susceptible to get infected.
Keywords: IDA with infection, Supernatant IL-2 and IFN?.